Design & Simulation of Enhanced Partial Shading System of a PV Module for Renewable Energy Plants (Eurasian Journal of Engineering and Technology, 2022)
The decisive influence of the decision of natural factors, in particular the strength of the radiation, remains an important limitation to consider while talking about the implementation of the constellation of nearby planets. Since the beginning of the solar cell manufacturing, this cell has faced many challenges, among them are manufacturing challenges and natural and abnormal challenges, and among the natural and abnormal challenges are partial or total shading of solar cells, which has affected significantly and directly in the production of solar cells from electrical energy. As a result, this natural or abnormal challenge prevented the optimal and full exploitation of solar energy, and through this research, I found a way to enhance the solar cell system with a simple system through which it can be linked to solar cells to enhance it and work in the production of electrical energy with or without shading of all kinds (natural and nonnatural). Or partial or total misrepresentation, and therefore the result also through this research was obtained electrical energy equivalent to twice the energy of solar cells with the presence or absence of misleading